Pengaruh Pemberian Tempe Dedak, Tape Dedak dan Kombinasinya Terhadap Nilai Ekonomi Ayam Broiler Fase Finisher - Osin, Merlinda; Suryatni, Ni Putu Febri; Theedens, Jonas F. (Yayasan Sumber Daya Manusia Cerdas, 2024)
he purpose of this study was to analyze the effect of giving tempeh bran, bran tape and their combination on the economic value of broiler chickens finisher phase. This study used 96 broiler chickens strain CP 707 aged 21 days. This research method uses a Complete Randomized Design (RAL) with 4 treatments and 6 repeats where each test consists of 4 broiler chickens. The experimental treatment was R0: basal ration + 20% rice bran (control), R1: basal ration + 20% tempeh bran, R2: basal ration + 20% bran tape, and R3: basal ration + combination of 10% tempeh bran + 10% bran tape. Data analysis is economic analysis which includes; production costs, receipts, profits, IOFC and BEP. The results of the analysis show that the treatment has a significant effect (P<0.05) on revenue, income and IOFC but has no significant effect (P>0.05) on production costs. It was concluded that the combination of 10% tempeh bran and 10% bran tape (R3) in the ration provided the best revenue, income and IOFC but had the same effect on the production costs of finisher phase broiler chickens.